2020
DOI: 10.1101/2020.05.11.20098673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Sex-Specific COVID-19 Clinical Outcomes

Abstract: To successfully mitigate the extraordinary devastation caused by the Coronavirus disease 2019 (COVID-19) pandemic, it is crucial to identify important risk factors for this disease. One such neglected health determinant is the sex of the patient. This is an essential clinical characteristic, as it can factor into a patient's clinical management and preventative measures.Some clinical studies have shown disparities in the proportion between males and females that have more severe clinical outcomes or, subsequen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…This study shows that the willingness of male residents in Chinese communities to be vaccinated is 1.48 times that of female residents in Chinese communities. The gender difference reflected by this vaccination may be related to the higher mortality rate of COVID-19 in men than in women, which is consistent with previous research results in China and internationally (17)(18)(19); a study (20) has reported that in the COVID-19 pandemic, women generally implement non-drug intervention measures such as wearing masks and washing hands frequently, so it can be summarized that men tend to vaccinate and women tend to use non-drug intervention to prevent COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that the willingness of male residents in Chinese communities to be vaccinated is 1.48 times that of female residents in Chinese communities. The gender difference reflected by this vaccination may be related to the higher mortality rate of COVID-19 in men than in women, which is consistent with previous research results in China and internationally (17)(18)(19); a study (20) has reported that in the COVID-19 pandemic, women generally implement non-drug intervention measures such as wearing masks and washing hands frequently, so it can be summarized that men tend to vaccinate and women tend to use non-drug intervention to prevent COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…47,48 The significant association of DM with COVID-19 severity in our study is similar to the results of a pooled analysis, which demonstrated that patients with DM had significantly higher risks of disease severity and mortality. 47 Across sex disparity, Galbadage and colleagues 49 indicated male sex as an essential risk factor for COVID-19 progression. By contrast, we found that the male group had notably lower severe disease compared with the female group.…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive association between male sex and acceptance of COVID-19 vaccination. Several independent reports demonstrate higher risks for COVID-19 complications, infectivity, and death among males [3]. While other sex-based health disparities such as cardiovascular disease, chronic respiratory disease, and cancer have been extensively reviewed [4], the sex-based difference in COVID-19 mortality may bias men to accept a vaccine.…”
Section: Discussionmentioning
confidence: 99%